2009
DOI: 10.1084/jem.20082584
|View full text |Cite
|
Sign up to set email alerts
|

T-bet is essential for encephalitogenicity of both Th1 and Th17 cells

Abstract: Abbreviations used: CNS, central nervous system; EAE, experimental autoimmune encephalomyelitis; MBP, myelin basic protein; MS, multiple sclerosis; NS, nonsense. The extent to which myelin-specific Th1 and Th17 cells contribute to the pathogenesis of experimental autoimmune encephalomyelitis (EAE) is controversial. Combinations of interleukin (IL)-1, IL-6, and IL-23 with transforming growth factor  were used to differentiate myelin-specific T cell receptor transgenic T cells into Th17 cells, none of which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
256
5
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 255 publications
(282 citation statements)
references
References 60 publications
20
256
5
1
Order By: Relevance
“…As measured by other studies [16,22,23], a remarkable proportion of Th17 cells also shares the ability to produce IFN-γ. These cells, producing both IL-17 and IFN-γ, are usually named Th17/Th1.…”
Section: Discussionsupporting
confidence: 62%
“…As measured by other studies [16,22,23], a remarkable proportion of Th17 cells also shares the ability to produce IFN-γ. These cells, producing both IL-17 and IFN-γ, are usually named Th17/Th1.…”
Section: Discussionsupporting
confidence: 62%
“…However, in the case of encephalitogenic T cells, we and others have found that myelin-specific Th17 cells differentiated with IL-6 and TGFb are not encephalitogenic (Yang et al, 2009;Ghoreschi et al, 2010;Lee et al, 2015). In fact, TGFb is a negative regulator of T-bet, a key transcription factor in encephalitogenic T cells, irrespective of whether it has a Th1 or Th17 phenotype (Gocke et al, 2007;Yang et al, 2009;Lee et al, 2015). Thus, suppression of the TGFb pathway enhances T-bet expression, as well as promotes the differentiation of pathogenic Th17 cells, suggesting that miRNAs that suppress TGFb signalling may promote the development of autoreactive effector T cells.…”
Section: Discussionmentioning
confidence: 54%
“…TGFb has been shown to promote the development of Th17 cells in the presence of IL-6 in mice (Bettelli et al, 2006;Mangan et al, 2006;Veldhoen et al, 2006), suggesting that diminished TGFb signalling may negatively modulate Th17 cells. However, in the case of encephalitogenic T cells, we and others have found that myelin-specific Th17 cells differentiated with IL-6 and TGFb are not encephalitogenic (Yang et al, 2009;Ghoreschi et al, 2010;Lee et al, 2015). In fact, TGFb is a negative regulator of T-bet, a key transcription factor in encephalitogenic T cells, irrespective of whether it has a Th1 or Th17 phenotype (Gocke et al, 2007;Yang et al, 2009;Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 70%
“…Neither overexpression of IL-17A in T cells nor its complete loss had an Correspondence: Dr. Lawrence Steinman e-mail: steinman@stanford.edu impact on clinical EAE [9]. More recently it has been shown that T-bet is more critical than IL-17 itself in the development of clinical EAE [10]. Thus, even though experiments in EAE were pivotal in defining the Th17 pathway, it is ironic that the role of IL-17 in EAE is highly controversial, (see Table 1.…”
Section: See Accompanying Article By Chen Et Almentioning
confidence: 99%